Understanding aims and values of science: Developments in the junior cycle specifications on nature of science and pre-service science teachers’ views in Ireland - Kelly, R; Erduran, S (Taylor and Francis, 2018)
Irish science education is aiming to develop post-primary students’ knowledge of and about science through the introduction of ‘nature of science’ (NOS) in the new junior cycle science specification. This study aimed to investigate pre-service science teachers’ views about a particular aspect of NOS, namely the aims and values of science. Aims and values in relation to science can be considered from epistemic, cognitive, cultural, social, political, moral and ethical perspectives. In this paper, we focus on the epistemic, cognitive and social aims and values of science to provide a broad overview and investigate pre-service science teachers’ understanding of them. Qualitative methods are used to highlight two case studies that provide an in-depth record of how pre-service science teachers interpret aims and values of science. Although the sample is limited in terms of its generalisability to pre-service teacher education at large, the study provides a framework for (a) what to target and investigate about NOS in science education, particularly about aims and values of science, and (b) how pre-service science teachers are likely to make sense of such relatively new curricular goals. Implications for pre-service science teacher education are discussed.